(untitled) (Physical Education, Health and Social Sciences, 2026)
This quasi-experimental trial investigated the effects of mental training programs on the attitude of the nurses about psychiatric patients. One hundred and twenty registered nurses in the public and private hospitals took part in four weeks of education based on interactive lectures, case discussions, and reflective exercises. The standardized Likert-scale questionnaire was adopted to measure the attitudes before and after the training. The findings showed that post-training attitude scores were significantly better than the pre-training attitude scores (p < .001), which is a positive change in attitude towards mentally ill people. The results indicate that mental health training is a useful intervention in reducing stigma, improving mental health literacy, and empathetic nursing practice. Since most nurses are employed in general healthcare environments where psychiatric comorbidities are prevalent, it is highly suggested to incorporate structured mental health education into the academic program and into continuing professional development programs. Enhancing the attitude of nurses toward psychiatric patients has the potential of eventually enhancing therapeutic relationships, as well as the quality of mental health care provision as a whole.